2022
DOI: 10.25259/jcis_47_2022
|View full text |Cite
|
Sign up to set email alerts
|

Transradial versus transfemoral arterial access in DEB-TACE for hepatocellular carcinoma

Abstract: Objectives Transradial access has become increasingly popular in body interventional procedures but has not been ubiquitously adapted. This retrospective study compares the efficacy of this approach versus transfemoral access in hepatocellular carcinoma (HCC) patients who underwent drug-eluting bead transarterial chemoembolization (DEB-TACE). Materials and Methods A total of 130 HCC patients underwent 146 DEB-TACE procedures within our institution from June 2015 to May 2020. About 90 and 56 procedures were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…This is consistent with the results of Ghosh et al who found no differences in terms of radiation dose between RAA (mean, 1578.9 mGy) and FAA (mean, 1383.0 mGy) ( P = .08) and in terms of fluoroscopy time (26.8 min vs. 24.8 min, respectively ( P = .23). 25 Similarly, Yamada et al reported no differences in median radiation dose given to the patient between RAA (811 mGy) and FAA (1200.5 mGy) ( P = .229) in 36 patients with HCC who underwent either transarterial bland embolization or TACE. 30 In a study involving 42 patients undergoing TACE with successive RAA and FAA, Iezzi et al found no significant differences in term of fluoroscopy time between RAA (399.6 ± 85.8 [SD] s) and FAA (356 ± 26 [SD] s) ( P = .071).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…This is consistent with the results of Ghosh et al who found no differences in terms of radiation dose between RAA (mean, 1578.9 mGy) and FAA (mean, 1383.0 mGy) ( P = .08) and in terms of fluoroscopy time (26.8 min vs. 24.8 min, respectively ( P = .23). 25 Similarly, Yamada et al reported no differences in median radiation dose given to the patient between RAA (811 mGy) and FAA (1200.5 mGy) ( P = .229) in 36 patients with HCC who underwent either transarterial bland embolization or TACE. 30 In a study involving 42 patients undergoing TACE with successive RAA and FAA, Iezzi et al found no significant differences in term of fluoroscopy time between RAA (399.6 ± 85.8 [SD] s) and FAA (356 ± 26 [SD] s) ( P = .071).…”
Section: Discussionmentioning
confidence: 93%
“…5 Similarly, Ghosh et al reported a 100% technical success rate between RAA (90/90) and FAA (56/56). 25 In another study, Wan et al reported 92.3% (24/26) technical success rate for hepatic arterial infusion chemotherapy using RAA and 100% (43/43) technical success rate using FAA in their retrospective cohort ( P = .139) and 100% technical success rate using RAA or FAA in their prospective cohort. 21 The same results were reported by Iezzi et al who found 100% technical success rates for TACE using either RAA or FAA.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Transradial access (TRA) has gained signi cant popularity over the years in body interventional procedures. Many studies have reported on the bene ts of TRA over transfemoral access (TFA) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%